Isolation and Characterization of Shewanella Phage Thanatos Infecting and Lysing Shewanella oneidensis and Promoting Nascent Biofilm Formation - Kreienbaum, Maximilian; Dörrich, Anja K.; Brandt, David; Schmid, Nicole E.; Leonhard, Tabea; Hager, Fabian; Brenzinger, Susanne; Hahn, Julia; Glatter, Timo; Ruwe, Matthias; Briegel, Ariane; Kalinowski, Jörn; et al. (Frontiers in Microbiology, 2020)
Species of the genus Shewanella are widespread in nature in various habitats, however, little is known about phages affecting Shewanella sp. Here we report the isolation of phages from diverse freshwater environments that infect and lyse strains of Shewanella oneidensis and other Shewanella sp. Sequence analysis and microscopic imaging strongly indicate that these phages form a so far unclassified genus, now named Shewanella phage Thanatos, which can be positioned within the subfamiliy of Tevenvirinae (Duplodnaviria; Heunggongvirae; Uroviricota; Caudoviricetes; Caudovirales; Myoviridae; Tevenvirinae). We characterized one member of this group in more detail using S. oneidensis MR-1 as a host. Shewanella phage Thanatos-1 possesses a prolate icosahedral capsule of about 110 nm in height and 70 nm in width and a tail of about 95 nm in length. The dsDNA genome exhibits a GC content of about 34.5 %, has a size of 160.6 kbp and encodes about 206 proteins (92 with an annotated putative function) and two tRNAs. Out of those 206, MS analyses identified about 155 phage proteins in PEG-precipitated samples of infected cells. Phage attachment likely requires the outer lipopolysaccharide of S. oneidensis, narrowing the phage’s host range. Under the applied conditions, about 20 novel phage particles per cell were produced after a latent period of approximately 40 minutes, which are stable at a pH range from 4 to 12 and resist temperatures up to 55 °C for at least 24 h. Addition of Thanatos to S. oneidensis results in partial dissolution of established biofilms, however, early exposure of planktonic cells to Thanatos significantly enhances biofilm formation. Taken together, we identified a novel genus of Myophages affecting S. oneidensis communities in different ways.